2018
DOI: 10.1039/c8ta01061g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical strain formation through anion substitution in Cu2WS4 for efficient electrocatalysis of water dissociation

Abstract: The electrocatalytic activity of ternary metal chalcogenides is improved by anion substitution that creates a chemical strain in the lattice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Recently, Tiwari et al [137] also used the previously reported selenium doping technique [64] in the Cu 2 WS 4 system to synthesize Cu 2 W(S y Se 1−y ) ( Figure 9b). The Tafel slope and overpotential at 10 mA cm −2 for the best sample (Cu 2 WS 1.3 Se 2.7 ) were reported to be 46 mV/dec and 320 mV, respectively.…”
Section: Quaternary Transition Metal Chalcogenides As Electrocatalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Tiwari et al [137] also used the previously reported selenium doping technique [64] in the Cu 2 WS 4 system to synthesize Cu 2 W(S y Se 1−y ) ( Figure 9b). The Tafel slope and overpotential at 10 mA cm −2 for the best sample (Cu 2 WS 1.3 Se 2.7 ) were reported to be 46 mV/dec and 320 mV, respectively.…”
Section: Quaternary Transition Metal Chalcogenides As Electrocatalystmentioning
confidence: 99%
“…(b) Schematic illustration of HER activity on Cu2W(S1−ySey)4 and corresponding polarization curves and Tafel plots for Cu2W(S1−ySey)4. Reprinted with permission from Reference[137], copyright (2018), Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…Because both mixed anion and mixed cation systems have shown better HER properties than their binary reference materials, combining these two approaches to create quaternary systems was a natural next step in electrocatalyst research. Recently, Tiwari et al [129] also used the previously reported selenium doping technique [62] in the Cu2WS4 system to synthesize Cu2W(SySe1-y) (Figure 9b). The Tafel slope and overpotential at 10 mA cm -2 for the best sample (Cu2WS1.3Se2.7) were reported to be 46 properties.…”
Section: Quaternary Transition Metal Chalcogenides As Electrocatalystmentioning
confidence: 99%
“…Strain effects can be used to tune the physical and chemical properties of materials. Recently the strain effects have been introduced to the research of electrocatalysis [26,[28][29][30][31][32][33][34][35][36] . For example, Zheng's group proposed that the formation of strained sulphur vacancies could activate and optimize MoS 2 basal planes for hydrogen evolution reaction [33] .…”
Section: Introductionmentioning
confidence: 99%